Introduction [in The Green Revolution reconsidered] - Hazell, Peter B. R.; Ramasamy, C. (International Food Policy Research Institute, 1991)
Agricultural technologies of the "green revolution" type have brought substantial direct benefits to many developing countries. Prominent among these has been increased food output, sometimes even in excess of the increasing food demands of a growing population. This has enabled food prices to decline in some countries, while in others prices have not risen as fast as they would have without the green revolution.